Tumor-related fungi and crosstalk with gut fungi in the tumor microenvironment - Yue Wang; Yiwen Wang; Yuhang Zhou; Yun Feng; Tao Sun; Junnan Xu (Cancer Biology & Medicine)
Most studies on the human gut microbiome have focused on the bacterial fraction rather than fungal biomics, which as resulted in an incomplete understanding of the fungal microbiome. Recent advances in microbiota detection and next-generation sequencing technology have boosted an increase in research on fungi. Symbiotic fungi have become increasingly influential in health and disease and modulate various physiologic functions within the host. Fungal infections can result in high morbidity and mortality rates and are life-threatening in some immunocompromised patients. In addition to bacterial dysbiosis, alterations in fungal communities are important and have been linked to many diseases, including asthma, mental illness, and various cancers. When investigating cancer it is imperative to consider the role of fungi alongside viruses and bacteria. This review examined the impact of intestinal fungi and peri-tumor fungi on tumorigenesis, cancer progression, and response to anticancer therapies. The review highlights the specific involvement of some fungal species in cancers include digestive tract tumors such as colorectal, pancreatic, liver, and gastric cancers, as well as non-digestive tract tumors such as lung, melanoma, breast, and ovarian cancers. Furthermore, fungal mechanisms of action, including fungus-host recognition and immune regulation, biofilm formation, toxin and metabolite production in the tumor microenvironment, and the complex effects of fungus-bacteria interactions on tumorigenesis and development, highlight the significance of potential biomarkers in cancer diagnosis and treatment.